Epidemic exposure, financial technology, and the digital divide - Saka, Orkun,Eichengreen, Barry,Aksoy, Cevat Giray (BOFIT, the Bank of Finland Institute for Emerging Economies, 2021)
We ask whether epidemic exposure leads to a shift in financial technology usage and who participates in this shift. We exploit a dataset combining Gallup World Polls and Global Findex surveys for some 250,000 individuals in 140 countries, merging them with information on the incidence of epidemics and local 3G internet infrastructure. Epidemic exposure is associated with an increase in remote-access (online/mobile) banking and substitution from bank branch-based to ATM activity. Heterogeneity in response centers on the age, income and employment of respondents. Young, high-income earners in full-time employment have the greatest tendency to shift to online/mobile transactions in response to epidemics. These effects are larger for individuals with better ex ante 3G signal coverage, highlighting the role of the digital divide in adaption to new technologies necessitated by adverse external shocks.
urn:nbn:fi:bof-202109282040
Keywords: Graue Literatur; epidemics; fintech; banking